2021
DOI: 10.1007/s41134-021-00173-1
|View full text |Cite
|
Sign up to set email alerts
|

The Dangers Associated with Female Adolescents Consuming Nyaope Drug in Butterworth, South Africa

Abstract: Nyaope is a potent drug that is currently challenging South Africa; its ramifications have destroyed the country’s youth. The study described in this paper sought to explore the dangers associated with the consumption of Nyaope in Butterworth, South Africa. This study adopted an explorative and descriptive qualitative approach that involved the facilitation of focus group discussions and one-on-one interviews with twenty-six participants. An analysis of the findings of the study revealed the health hazards ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Nyaope's abuse is not just endemic, but has ripple effects that extend beyond individuals' health to include social spheres, families, 7 and society. [8][9][10][11] There are several similar psychoactive agents and locally produced cocktails and illicit drugs that are abused in several African countries or other parts of the world. It is thus clear that global efforts that are channeled toward addressing problems of drug epidemiology have been premised largely on the classical understanding of drug epidemiology from the developed part of the world.…”
Section: Drug Epidemiology As a Critical Topic In Health Equitymentioning
confidence: 99%
“…Nyaope's abuse is not just endemic, but has ripple effects that extend beyond individuals' health to include social spheres, families, 7 and society. [8][9][10][11] There are several similar psychoactive agents and locally produced cocktails and illicit drugs that are abused in several African countries or other parts of the world. It is thus clear that global efforts that are channeled toward addressing problems of drug epidemiology have been premised largely on the classical understanding of drug epidemiology from the developed part of the world.…”
Section: Drug Epidemiology As a Critical Topic In Health Equitymentioning
confidence: 99%
“…In South Africa, research has shown that stigma is generally more associated with people who use substances than with people who live with other mental disorders, and this is partly attributed to personal culpability associated with SUDs [ 15 ]. The use of heroin and heroin mixed with other substances is highly stigmatised, leading to marginalisation of people using substances, and rejection by their families and communities [ 16 ]. It has been observed that greater stigma is also attached to particular treatment methods, such as opioid substitution treatment (OST) [ 17 ], and other harm reduction interventions such as needle-and-syringe-exchange programmes.…”
Section: Introductionmentioning
confidence: 99%
“…According to statistics, drug consumption in SA is nearly twice that of the rest of the world and it is the highest in Africa (Charlton et al 2019 ). A steady increase in the consumption of several drugs has caught SA off guard, with nyaope leading the way (Bala & Kang’ethe 2021 ). Despite the rise in the prevalence of nyaope through smoking and injections in SA, the South African government has not fully embraced the harm reduction approach as one of the frameworks for addressing the public health concerns that are unavoidably associated with the use of nyaope (Lefoka & Netangaheni 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The stigmatisation contributes to communities distancing themselves from individuals who use drugs and being afraid of those with drug use difficulties, viewing them as dangerous (Paquette, Syveertsen & Pollini 2018 ). Those who use nyaope are the most stigmatised amongst key populations in SA, limiting their access to healthcare and protection (Bala & Kang’ethe 2021 ). This is further fuelled by the traditional stereotypes that hold women to different expectations and roles as mothers, partners and caretakers, women who inject drugs are stigmatised more than men (El-Bassel & Strathdee 2016; Khuat et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation